Mahasiswa Kesejahteraan Sosial FISIP USU Meningkatkan Minat Baca Anak Panti - Michael Doloksaribu (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2022)
The author did practicum II at the Ora Et Labora Nusantara Orphanage. The second practicum carried out by the author was to examine the problems experienced by orphans. The problems experienced by orphanages are the lack of reading culture so that they have difficulty in learning. Especially during the current pandemic, children prefer to spend time playing with their friends at the orphanage rather than taking the time to study. From this problem, the author is interested and has the aim of increasing interest in reading for orphans which is a mini project from this author on education to children. The author has a client (group) who is experiencing this problem. The group consists of children who are still in elementary school (SD). The author uses the stages of social groupwork in his research from the preparation stage to the termination stage. The method used is the Delphi method using Focus Group Discussion (FGD). After doing all the stages of social groupwork, the results are presented by the author so that the orphanage children can continue the reading culture so that they have no difficulty in learning at school.